Tranexamic acid in hip fracture surgery: A systematic review and meta-analysis. (13th December 2019) - Haj-Younes, Bashar; Sivakumar, Brahman S; Wang, Michael; An, Vincent VG; Lorentzos, Peter; Adie, Sam
Aims: The primary objective of this review was to determine whether tranexamic acid (TXA) reduces transfusion rates in patients undergoing surgery for hip fractures. The secondary objective was to assess the effects of TXA on mortality and thromboembolic events in the same cohort. Methods: A systematic review of electronic databases was performed in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We included randomized controlled trials comparing perioperative TXA in patients treated surgically for hip/proximal femoral fractures against placebo. The primary outcome was the proportion of patients requiring blood transfusion. Secondary outcomes were blood loss, mortality, and complications. Meta-analysis was performed using inverse variance and random effects model. Results: The pooled data from 10 studies involving 842 patients showed that the proportion of patients requiring blood transfusion was significantly less in the TXA group (risk ratio (RR) 0.72, 95% confidence interval (CI) 0.59–0.88). There was no difference between TXA and control groups when comparing mortality (RR 1.17, 95% CI 0.65–2.10), deep venous thrombosis (RR 1.14, 95% CI 0.43–3.06), pulmonary embolism (RR 0.53, CI 0.09–3.02), acute coronary syndrome (RR 1.52, CI 0.18–12.98), cerebrovascular events (RR 0.78, CI 0.16–3.68), or wound complications (RR 1.61, CI 0.51–5.13). Conclusion: There is evidence that TXA reduces the proportion of patients requiring blood transfusions when undergoing hip fracture surgery. However, the small sample size and low event rates for adverse effects preclude any definitive conclusions from being established regarding adverse effects. Future trials should be powered to further assess potential complications and determine the ideal dosage and regime.